Comparison of Crop Simulation and Field Performance of Maize Under 20-day Dry Period Imposed During Selected Critical Growth Periods in Nakhon Ratchasima Province, Thailand - S. Jampatong2, L. Samarakoon1, A. Noomhorm1, R. S. Clemente1, D. B. Hannaway3, K. Thongsaga1, S.L. Ranamukhaarachchi1* (Recent Research in Science and Technology, 2010)
Untimely prolonged dry spells hamper not only the already established maize crop (Zea mays L.), but also the farmers’ decision making on the succeeding crop. This study was conducted to determine the effect of a 20-day dry period during selected critical growth stages on growth and yield of maize, and apply the CERES-Maize model in DSSAT version 4.0.2.0. Five 20-day dry periods coinciding with selected critical growth stages [viz. 21-40 days from seeding (DFS), 30-49 DFS, 36-55 DFS, 43-62 DFS and 57-76 DFS] were compared with a control treatment maintained with weekly irrigation using two popular maize cultivars (‘Suwan 4452’ and ‘Pacific 224’) in a factorial experiment using a split plot design with four replicates. Soil moisture content (SMC) at 0-15 and 15-30 cm depths reached the lowest limit of readily available water (RAW) in eight days after suspension of irrigation, but did not reach permanent wilting point (PWP) during the remaining 12 days. Both leaf area index (LAI) and plant height were significantly decreased (p=0.05) in treatments subjected to a dry period during 21-40 and 30-49 DFS. Grain number per cob, grain yield and harvest index (HI) decreased significantly (11.3%, 11.2% and 13.5%, respectively) when the dry period imposed only occurred during 21-40 DFS. ‘Suwan 4452’ had a higher grain number per cob than ‘Pacific 224’, but 100-grain weight was higher for ‘Pacific 224’cultivar. The CERES-Maize model showed excellent performance in predicting the time to silking and physiological maturity, 100-grain weight, grain yield and HI. Simulated values of LAI and number of grains per cob showed greater variability based on standardized bias (R) and standardized mean square error (V). Overall, however, the CERES-Maize model was useful in providing approximate information enabling appropriate decision making in the event of dry periods extending up to 20-days.